Recent Advancement in Feature Extraction tools for Biometric System: Comparative Analysis - Sharma, Om Prakash; Sheetlani, Jitendra; Shrivastava, Praveen (International Journal of Computer Sciences and Engineering, 2019)
Biometrics is the new technology for body measurements and calculations that is use to identifying a person. It signifies to metrics related to human physiological or behavioral characteristics. Many specific physiological and behavioral parts, personal characteristics have been suggested and used for biometric security scheme [1]. Any Biometric system comprises of four modules: sensor module, feature extraction module, database module and matching module. Out of all these module feature extraction module of any recognition system plays an important role in recognizing the particular objects with same set of images [3]. This paper presents an analysis on the use of the newly introduced modern and popular key-points feature extracting tools and methodologies that can be applicable in the biometric domain. The implementation is carried out using MATLAB programming environment and tested on CASIA database for Iris and FVC2004 DB3_A for Fingerprint.